RANCANG BANGUN MESIN PEMBUAT MARSET ALAS VELG TRUK YANG EFEKTIF DAN EFISIEN DENGAN ANALISIS KANSEI ENGINEERING - Betha Sanjaya; Mathilda Sri Lestari; Ainur Komariah (LP3M, 2022)
The increase in the number of motorcycle transportation resulted in the amount of waste tires in used motorcycles amounting to 14.4 and 15.4 tons/day, respectively. This increasing number has the potential to cause waste tire pollution which has an adverse impact on the environment. The waste tires can be processed into marset. Therefore, it is necessary to design an effective and efficient marset making machine using the Kansei engineering method which aims to improve the marset making machine in the home industry of marsett in Klaten Regency. The results of this study are the results of validity and reliability tests on 10 kansei words obtained from the survey, including Strong, Durable, Colored, Safe, Good Quality, Fast, Efficient, Easy to Operate, Modern, and Easy to Clean. Of the 10 kansei words that have a calculated r value greater than r table and the result value of cronboach alpha (α) is 0.941, then the data is declared valid and reliable. The results of the conjoint analysis research show that of the 10 categories selected, namely square, iron, 250 Watt electric motor, lever system and the number of rollers there are 2 rolls. By using the new marset making machine, the increase in production for 1 week was 250 units/ 327%.